+0  
 
0
175
1
avatar+3650 

Help.

NotSoSmart  Jan 14, 2018
 #1
avatar+91071 
0

(-3i) (-4i)  =

 

-3 * - 4  * i * i   =

 

12  * i^2           ⇒ [ i^2  = -1  ]

 

12 * -1  =

 

-12

 

 

x + y  =  5   ⇒   y  =  5  - x     (1)

x^2  + y^2  =  25     (2)

 

Sub  (1)  into (2)

 

x^2  +  ( 5 - x) ^2   =  25

x^2  + x^2  - 10x  +  25  = 25   subtract 25 from both sides

2x^2  - 10x  = 0    factor

2x ( x  - 5)      set both facoters to 0 and solve for x and x  =  0   or  x  = 5

 

 

Using (1)

 

When x  = 0,     y  =  5 - 0   =  5

and

When  x  = 5,  y  = 5 - 5  =   0

 

So the solutions are    (0, 5)  and  (5, 0 )

 

 

cool cool cool

CPhill  Jan 14, 2018

21 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.